Force and number of myosin motors during muscle shortening and the coupling with the release of the ATP hydrolysis products. (7th July 2015) - Caremani, Marco; Melli, Luca; Dolfi, Mario; Lombardi, Vincenzo; Linari, Marco
Abstract : Key points: Muscle contraction is due to cyclical ATP‐driven working strokes in the myosin motors while attached to the actin filament. Each working stroke is accompanied by the release of the hydrolysis products, orthophosphate and ADP. The rate of myosin–actin interactions increases with the increase in shortening velocity. We used fast half‐sarcomere mechanics on skinned muscle fibres to determine the relation between shortening velocity and the number and strain of myosin motors and the effect of orthophosphate concentration. A model simulation of the myosin–actin reaction explains the results assuming that orthophosphate and then ADP are released with rates that increase as the motor progresses through the working stroke. The ADP release rate further increases by one order of magnitude with the rise of negative strain in the final motor conformation. These results provide the molecular explanation of the relation between the rate of energy liberation and shortening velocity during muscle contraction. Abstract: The chemo‐mechanical cycle of the myosin II–actin reaction in situ has been investigated in Ca 2+ ‐activated skinned fibres from rabbit psoas, by determining the number and strain ( s ) of myosin motors interacting during steady shortening at different velocities ( V ) and the effect of raising inorganic phosphate (Pi ) concentration. It was found that in control conditions (no added Pi ), shortening at V ≤ 350 nm s –1 per half‐sarcomere, corresponding to force ( T ) greater than half the isometric force ( T 0 ), decreases the number of myosin motors in proportion to the reduction of T, so that s remains practically constant and similar to the T 0 value independent of V . At higher V the number of motors decreases less than in proportion to T, so that s progressively decreases. Raising Pi concentration by 10 mm, which reduces T 0 and the number of motors by 40–50%, does not influence the dependence on V of number and strain. A model simulation of the myosin–actin reaction in which the structural transitions responsible for the myosin working stroke and the release of the hydrolysis products are orthogonal explains the results assuming that Pi and then ADP are released with rates that increase as the motor progresses through the working stroke. The rate of ADP release from the conformation at the end of the working stroke is also strain‐sensitive, further increasing by one order of magnitude within a few nanometres of negative strain. These results provide the molecular explanation of the relation between the rate of energy liberation and the load during muscle contraction.